Applying AcciMap to test the common cause hypothesis using aviation near misses. (September 2020) - Thoroman, Brian; Salmon, Paul; Goode, Natassia
Abstract: The common cause hypothesis, as applied here, proposes that similar networks of influencing factors may contribute to both adverse outcomes and near misses. This hypothesis has not been evaluated using a systems-thinking perspective. The aims of this study are to evaluate whether networks of contributory and protective factors exist within aviation serious near miss reports and to determine if the common cause hypothesis is applicable in this context. Sixteen incident reports from French civil aviation crash investigation bureau were analysed using the AcciMap method. Contributory and protective factors, and relationships between both were identified via coding of the reports. The results indicate that considering protective factors support a richer picture of incidents and provide support for the common cause hypothesis as measured by similar mean factor volume and sociotechnical levels for both contributory and protective factors. However, the findings also show the direction of relationships among protective and contributory factors may be indicative of a difference among adverse outcomes, near misses, and normal work. Future research should consider how a network of relationships may impact on the common contributory and protective factors found in near misses. Highlights: We analysed aviation near miss incidents to identify contributory and protective factors. AcciMaps were used to identify networks of factors for each incident. The findings were used to evaluate the common cause hypothesis. Protective and contributory factors in near misses share similar categorization. Factor relationships may be indicative of near misses versus adverse outcomes.